Saving Private Ryan - Spielberg, Steven, 1947-; Bryce, Ian; Gordon, Mark, 1956-; Levinsohn, Gary; Rodat, Robert; Hanks, Tom; Burns, Edward, 1968-; Damon, Matt; Sizemore, Tom, 1961- (DreamWorks Home Entertainment, 1999)
Captain John Miller must take his men behind enemy lines to find Private Ryan, whose three brothers have been killed in combat. Faced with impossible odds, the men question their orders. Why are eight men risking their lives to save just one? Surrounded by the brutal realities of war, each man searches for his own answer and the strength to triumph over uncertain future with honor, decency and courage.